Efektivitas Penggunaan Aplikasi Quizizz untuk Meningkatkan Motivasi Berprestasi Mahasiswa pada Pembelajaran Daring - Eka Ary Wibawa; Arif Rahman Hakim; Rahmat Darmawan; Anita Anggraini (Universitas Indraprasta PGRI Jakarta, 2022)
The purpose of this research is to determine the effectiveness of using the Quizizz application in increasing student achievement motivation in online learning. This is quasi-experimental research with a quantitative approach. The research was conducted in the even semester of the 2021/2022 academic year at the Accounting Education Study Program, Faculty of Economics, UNY. The research sample consisted of an experimental class consisting of 32 students and a control class consisting of 32 students. The instrument of data collection was done with a closed questionnaire which was developed referring to the Likert scale with five alternative answers. The independent sample t-test was used to analyze the data. The findings demonstrated that the Quizizz application's effectiveness in boosting student achievement motivation significantly. The implication is that if the lecturer intends to increase student achievement motivation, they can use the Quizizz application in learning assessment.